An exploratory examination of reflective thinking in certified human performance improvement professionals - Buck, Joel A. (Kansas State University, 2017)
This exploratory study investigated reflective thinking by professionals in the workplace and relationships between participant demographics and reflective thinking. The Questionnaire for Reflective Thinking (QRT) was used to assess the quality of reflective thinking in a sample (n = 102) of individuals certified by the International Society for Performance Improvement (ISPI) as Certified Performance Technologists (CPT) (N = 697). Business leaders seek employees who practice reflective thinking. Employers and students expect college coursework to provide the needed skills and educators recognize this need. Researchers have developed reliable measures of reflective thinking, but the quality of reflective thinking practiced by professionals in the workplace is not known. Hierarchical multiple regression analysis was used to examine QRT scores for habitual action, understanding, reflection, and critical reflection, with respect to the demographic variables of gender, age, years of experience, education level, and academic discipline. Significant relationships between age and scores for habitual action, experience and scores for habitual action, education level and scores for understanding, gender and scores for critical reflection, and experience and scores for critical reflection were identified. No other differences in QRT scores based on the independent variable gender, age, experience, education level, or academic discipline were statistically significant.
Keywords: Reflective thinking; Critical thinking; Questionnaire for Reflective Thinking; Certified Performance Technologist; Reflective thinking in workplace